2007
DOI: 10.1002/jcop.20141
|View full text |Cite
|
Sign up to set email alerts
|

Support for military families and communities

Abstract: This is a call for community psychologists to engage in research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…Although it may once have been the case that military support systems alone could thoroughly address the needs of military families, the closing of many military installations, the expanded role of the reserve component, financial constraints posed by the federal sequester, and the longest war in our nation's history mean that this is no longer the case. The current study is consistent with three of the research priorities identified by Hoshmand and Hoshmand (2007): it assesses potential stressors impacting military families in the form of specific risk factors; it considers community strengths and needs; and it considers children's resilience in the form of positive outcomes despite adverse experiences. The ecological perspective (Bronfenbrenner & Morris, 2006) reinforces these priorities because it emphasizes that influences on children's functioning include not only microsystems like the family, where developing individuals participate directly, but also exosystems like parents' work environments and community organizations that are more distal to children.…”
Section: Risk and Promotive Factorssupporting
confidence: 57%
See 1 more Smart Citation
“…Although it may once have been the case that military support systems alone could thoroughly address the needs of military families, the closing of many military installations, the expanded role of the reserve component, financial constraints posed by the federal sequester, and the longest war in our nation's history mean that this is no longer the case. The current study is consistent with three of the research priorities identified by Hoshmand and Hoshmand (2007): it assesses potential stressors impacting military families in the form of specific risk factors; it considers community strengths and needs; and it considers children's resilience in the form of positive outcomes despite adverse experiences. The ecological perspective (Bronfenbrenner & Morris, 2006) reinforces these priorities because it emphasizes that influences on children's functioning include not only microsystems like the family, where developing individuals participate directly, but also exosystems like parents' work environments and community organizations that are more distal to children.…”
Section: Risk and Promotive Factorssupporting
confidence: 57%
“…Here, while both kinds of risk were important, normative risk factors such as minority status were more strongly related than military-specific risks to outcomes for youth in military families. Hoshmand and Hoshmand (2007) call on community psychologists to pay greater attention to military families, in part because most military families-regardless of whether they serve in the active or reserve component-live, work, receive medical care, and are educated in civilian communities. Although it may once have been the case that military support systems alone could thoroughly address the needs of military families, the closing of many military installations, the expanded role of the reserve component, financial constraints posed by the federal sequester, and the longest war in our nation's history mean that this is no longer the case.…”
Section: Risk and Promotive Factorsmentioning
confidence: 99%
“…These individuals represent an under-studied group in the literature (Houston et al 2009;Mansfield 2009) and are in a unique position as ''citizen soldiers.'' They face challenges that full-time service members do not, such as navigating civilian employment (Griffith 2010), potentially significant drops in financial income when mobilized (Hoshmand and Hoshmand 2007), isolation and a separation from unit affiliation (Wiens and Boss 2006), and limited access to formal support resources provided by the military (Lapp et al 2010). Thus, National Guard and Reserve personnel and their families are more vulnerable than other military professionals (Kline et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…This focus on community as a leverage point for supporting service members and families was fueled by a shift in human service delivery systems toward outsourcing and privatization of traditional installation support functions, including an increase in the percentage of military families residing off-base and receiving services in the civilian community, and a related perception among military leaders about a loss in "sense of community" among its members and families (Hoshmand & Hoshmand, 2007;Martin & Sherman, 2009). At the same time, research was demonstrating positive associations between community support, sense of community, and service member and family adaptation to the demands of military life (Bowen, Mancini, Martin, Ware & Nelson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This "science" includes both basic research that seeks to identify social antecedents and correlates of desired outcomes for service members and families, and evaluation research that examines the application and effectiveness of interventions targeted to influence these antecedents and correlates (Fraser & Galinsky, 2010). The current investigation focuses on the front end of this research sequence and, in part, represents a response to the call by Hoshmand and Hoshmand (2007) for community psychologists "to The Willingness of Military Members to Seek Help: The Role of Social Involvement and Social Responsibility engage in research, consultation, and program development and evaluation in supporting military families and communities" (p. 171).…”
Section: Introductionmentioning
confidence: 99%